5m+7=6x

Simple and best practice solution for 5m+7=6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5m+7=6x equation:


Simplifying
5m + 7 = 6x

Reorder the terms:
7 + 5m = 6x

Solving
7 + 5m = 6x

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + -7 + 5m = -7 + 6x

Combine like terms: 7 + -7 = 0
0 + 5m = -7 + 6x
5m = -7 + 6x

Divide each side by '5'.
m = -1.4 + 1.2x

Simplifying
m = -1.4 + 1.2x

See similar equations:

| -3+3k=4k-13 | | 5a+10=-2a+24 | | 5x+4=-20+3x | | a+5=5a-3 | | 2b-8=-8+b | | w+3=3w-17 | | 2w-1=-19+4w | | 18=3(3*-6) | | 5(x-2)=3(x+1) | | -m+9=5m-45 | | -k+10=k+26 | | -4x-24=4 | | 8+5x=-6x+52 | | k-8=52-5k | | 2k-2=5k+1 | | -7w+8=-56+w | | -4-3w=2w-14 | | 5x-1=4x+2 | | -10(2x-14)-6x=70 | | -6m+4=2m+84 | | -5+6d=-6d+127 | | -k-6=3k+22 | | -7b+8=-2b-17 | | -3a+4=4a+39 | | 5a+8=-2+4a | | -6m-8=6+m | | y=-2/5-3 | | 3d+2=5d-22 | | 6x+4=94-3x | | a+5=6a+50 | | -8-2d=6d-16 | | -4+5n=6n-6 |

Equations solver categories